2020
DOI: 10.33545/gynae.2020.v4.i1b.448
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of correlation between body mass Index with menstrual cycle pattern among young female medical students

Abstract: Introduction: Adolescence is a period of maturity, a point of physical, emotional, social and psychological change. Menstruation is described as the exclusive sign of femininity and it is a physical manifestation of complex endocrine axis. Body mass index or BMI have the most control over menstrual irregularity. The increasing trends in the prevalence of childhood obesity, early puberty and menarche, and ethnic racial differences in the effect of body mass index on the reproductive characteristics of young fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…A study conducted by Dars et al from Pakistan revealed that 67.33% of the girls had their first menstrual period between the age of 11 and 13 (mean ¼ 12.92 years, standard deviation of 1.41 years) 1 Similar study result reported by Rai et al from India revealed that the average age of menarche was 13.5 years with a standard deviation of 1.35. 2 Ramraj et al from Pune also reported similar findings that age of menarche was 12 years. 3 Another study results also showed similar results as present study like the mean age at menarche was 12.59 (AE 1.86) years study report by Ganesan et al 4 So, we conclude that the average age of menarche is between the ages of 11 and 13 years based on data from both previous studies and this study.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…A study conducted by Dars et al from Pakistan revealed that 67.33% of the girls had their first menstrual period between the age of 11 and 13 (mean ¼ 12.92 years, standard deviation of 1.41 years) 1 Similar study result reported by Rai et al from India revealed that the average age of menarche was 13.5 years with a standard deviation of 1.35. 2 Ramraj et al from Pune also reported similar findings that age of menarche was 12 years. 3 Another study results also showed similar results as present study like the mean age at menarche was 12.59 (AE 1.86) years study report by Ganesan et al 4 So, we conclude that the average age of menarche is between the ages of 11 and 13 years based on data from both previous studies and this study.…”
Section: Discussionmentioning
confidence: 66%
“…The cycle length was 29.79 days with standard deviation of 4.87. 2 Another study reported by Zohora reported that out of the 250 respondents, most of them reported their menstruation duration range between 4 and 7 days (80.8%), 72.4% had regular menstrual cycles, and the length of the menstrual cycle of the 127 respondents (50.8%) was 21 to 35 days. Moderate blood flow was reported by 62% of respondents, 24% had heavy blood flow, and 14% had scanty or little blood flow.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in a study examining the prevalence of menstrual cycle disorders in physically active women with a BMI of less than 18.5 kg/m 2 , half of the underweight women reported menstrual cycle disorders [ 34 ]. Additionally, a study conducted on medical students aged 18–25 years reported a relationship between low BMI and irregular menstrual cycles [ 35 ], and a study conducted on female college students aged 18–26 years also reported a relationship between low body weight and irregular menstrual cycles [ 36 ]. In this study, the relationship between being underweight and menstrual cycles was not found.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be related to the subjects. Most of the participants in studies that reported a relationship between being underweight and menstrual cycles were female college students and adolescents [ 35 37 ]. The poor nutritional status of young women appears to have a greater impact on the menstrual cycle, which may be related to the different age groups in this study.…”
Section: Discussionmentioning
confidence: 99%